2016
DOI: 10.1002/14651858.cd011812.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Factors that impact on the use of mechanical ventilation weaning protocols in critically ill adults and children: a qualitative evidence-synthesis

Abstract: 2016). Factors that impact on the use of mechanical ventilation weaning protocols in critically ill adults and children: a qualitative-evidence synthesis. Cochrane database of systematic reviews (Online), (10).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 85 publications
2
35
0
2
Order By: Relevance
“…Given that data on treatment outcomes generated by local clinical trials is rarely available, health professionals [46][47][48]. Local characteristics require that bundles and protocols developed in resource-rich countries be adapted before implementation in resource-limited settings [49,50]. For example, most sub-Saharan countries lack resources to implement all components of the Surviving Sepsis Campaign Guidelines, but local modification might allow the implementation of specific life-saving interventions [51].…”
Section: Gaps In Evidence For Best Practicesmentioning
confidence: 99%
“…Given that data on treatment outcomes generated by local clinical trials is rarely available, health professionals [46][47][48]. Local characteristics require that bundles and protocols developed in resource-rich countries be adapted before implementation in resource-limited settings [49,50]. For example, most sub-Saharan countries lack resources to implement all components of the Surviving Sepsis Campaign Guidelines, but local modification might allow the implementation of specific life-saving interventions [51].…”
Section: Gaps In Evidence For Best Practicesmentioning
confidence: 99%
“…In a large international survey on peri-extubation practices (112/162 NICUs), most respondents chose 24 (30%), 48 (22%), or 72 h (41%) [27]. Finally, clinician perceived lack of efficacy or awareness, NICU culture and policies, and overlooking/overemphasising clinical judgement may contribute to variability in extubation practices [28].…”
Section: Introductionmentioning
confidence: 99%
“…Although it may be difficult to observe similarities in barriers when comparing individual studies, the use of a conceptual framework such as CFIR allows implementation researchers to classify barriers into major domains and themes. As Table 1 [10 ▪▪ ,38 ▪▪ ,39 ▪▪ ,4042 ▪ ,48 ▪▪ ,49 ▪▪ ,53 ▪▪ ]demonstrates, the recent literature has identified a multitude of barriers that fall within all five CFIR domains, although most studies have investigated barriers in the inner setting and individuals domains. Having a systematically derived catalog of barriers allows implementation researchers and clinicians to design and evaluate implementation strategies that are targeted correctly, allowing for the greatest chance of success in improving the adoption of evidence-based practice.…”
Section: Resultsmentioning
confidence: 99%
“…Jordan et al [40 ▪ ] conducted a qualitative evidence review of 11 studies that reported on the facilitators and barriers to implementation of protocols for ventilator weaning. Many barriers were identified, and can be grouped into three themes: barriers related to clinician knowledge and personal values and priorities (CFIR individuals), barriers related to practical arrangements for care such as ICU structure, resources, and staffing (CFIR inner setting), and professional practice such as training and experience, perceived confidence, and inter-professional relationships (CFIR individuals, inner setting, and process).…”
Section: Bundled Management Of Mechanically Ventilated Patientsmentioning
confidence: 99%